Oral Care Needs Amongst Disadvantaged Migrants in France - Camille Pichemin; Emile Boyer; Pascal Jarno; Valérie Bertaud; Vincent Meuric; Antoine Couatarmanach (Elsevier, 2022)
Background: Disadvantaged migrant populations face risk factors that can affect their oral health amongst other health issues. The purpose of this study was to explore the oral care needs of these populations and to identify the obstacles they might encounter in accessing dental care. Methods: A cross-sectional study using secondary data was carried out in the Centre Médical Louis Guilloux in Rennes, France, a health centre offering dental consults to migrants. The data were obtained by clinical oral examination and analysed according to various criteria: reason for consultation, diagnosis, treatment plan, drug prescriptions, and referrals to other practitioners. Results: A high prevalence of decay was observed amongst the patients (72.3%). Fifty-nine patients were identified as needing major oral health care amongst the 130 files that were analysed. The lack of proficiency in the host country's language was associated with a major need for oral care (P < .02). Conclusions: This study highlights that disadvantaged migrants face important oral care needs in France. It suggests alternative actions that should be carried out to improve their access to dental care, including access to interpreting.